(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article presents the opinions of domestic and foreign scientists about modern methods of plastic surgery. In order to satisfy cosmetic and reconstructive demands, modern plastic surgery procedures have greatly advanced, becoming safer, more effective, and less intrusive. Modern cosmetic surgery procedures have changed dramatically, combining cutting-edge medical technology with sophisticated approaches to enhance patient happiness, safety, and results.